The [flourishing] entrepreneur: a case for legislative intervention to support healthy SMME financial access in South Africa - Bryce, Richard James (Department of Commercial Law, 2017)
This thesis presents human flourishment as the theoretical foundation from which to pursue social policy in the post-colony. Accepting this theoretical foundation, the purpose of this thesis is to reflect on the role and potential of small, micro and medium enterprises (SMMEs) in South Africa. Further, this thesis will consider in what manner the law can support the realisation of the potential of South African SMMEs. The main value of this thesis is to illustrate the positive distributional impact that a human flourishment approach to legal intervention can have for a property system, which has the objective of supporting the realisation of the capabilities of persons in society. This value is illustrated in this thesis by analysing the relationship between the South African SMME and retail banking sectors. This thesis has chosen to focus on the SMME sector because of the role identified for SMMEs in South Africa's growth strategy, the National Development Plan (NDP). This role includes recognising SMMEs as being an entry point for previously excluded persons into the mainstream economy. A recent report by the Small Enterprise Development Agency (SEDA) highlights that the potential of SMMEs in South Africa remain unrealised. The report identifies key barriers to SMME flourishment in South Africa. This thesis focuses on the following identified barriers in the report: (i) the existing legal framework with respect to SMMEs; (ii) existing government agency support available to SMMEs; and (iii) the ability of SMMEs to access finance and credit. A primary finding in this thesis is existing credit structures in the retail banking sector are negatively biased towards the black population group. This has an adverse impact on black entrepreneurs. It is suggested in this thesis that this negative bias is a consequence of apartheid. Apartheid had the effect of regulating the access that black people had to the mainstream economy and their ability to acquire and accumulate property. Recognising that SMMEs have an identified role to play in South Africa's growth strategy, this thesis finds that legislative intervention in the retail banking sector is needed in order to overcome this negative bias and to support increased SMME access to finance and credit. This thesis interprets the preamble to the Constitution, as well as the concept of transformative constitutionalism, as mandating a capabilities-approach to human development. It is for this reason that a property system with a distributional outcome that supports the realisation of the capabilities of persons in society is preferred by this thesis. It is only once there is a real commitment of moving the majority of South Africans into the mainstream economy will inroads to tackling inequality and poverty be made.